ANALYSIS THE EFFECTIVENESS OF WOMEN EMPOWERMENT THROUGH A NATIONAL PROGRAM OF COMMUNITY EMPOWERMENT (PNPM) VILLAGE SINARSARI, DRAMAGA - BOGOR - Wartoyo Hadi; Siti Noeraeni (The Management Journal of Binaniaga, 2016)
The development of micro business mother household in Sinarsari village districts Dramaga Bogor districts is part village economic potential due it was a significant change, saw income housewives fueled the family income, then should to have competent involved in coaching. Based on two different test mean in pairs, the results of the analysis showed that they have had different the average income and profit has increased after there are PNPM program Mandiri Perdesaan through. Thus the increase in earnings from the effort is mean the empowerment of women had been operating effectively, hence then it is suggested that continue to be increased again guidance and the granting of loans revolving funds to housewives and for those who have no sector needed to have the information on the program, but within consideration of the community capacity concerned.Keywords: Effectiveness, empowerment of women, PNPM Mandiri.